Parameters and genetic tendency in post-weaning growth traits in Santa Gertrudis males - Morales, Y.; Guerra, Danilo; Su?rez, M. A.; Rodr?guez, M.; Gonz?lez-Pe?a, Dianelys; Ramos, F. (Cuban Journal of Agricultural Science, 2013)
For estimating the parameters and genetic tendencies of post-weaning growth traits of Santa Gertrudis males, the performance test records of the period 1981-2010 were analyzed. Records came from the cattle breeding enterprises ?Turiguan?? and ?Camilo Cienfuegos?, from Ciego de ?vila and Pinar del R?o, respectively, as well as from the cattle breeding farm ?Rancho Vallina?, of Santiago de Cuba. Live weight traits were studied at the beginning of the performance test (ILW), average daily gain (ADG), weight for age (WFA) and final live weight in the performance test (FLW), at 18 months. Animals were fed natural pastures and supplemented with concentrates. The analysis was carried out through a multi-trait animal model, including as fixed effects the contemporary group (herd-year-birth trimester) and age as covariable. As random effects the direct and maternal additive genetic effects and the residual error were considered. The highest heritability estimates were of 0.21 ? 0.07 and 0.22 ? 0.07 for FLW and WFA, respectively. The genetic correlations between ADG and WFA were 0.78 ? 0.21 and between ILW and ADG 0.83 ? 0.07. The lowest correlation was between ILW and FLW (0.60). It is concluded that heritabilities for growth traits in Santa Gertrudis cattle were between medium and low. Genetic correlations were high and positive. Genetic tendencies resulted low; there was no genetic progress in traits as ADG. Key words: final live weight, direct and maternal effects, genetic progress